1998
DOI: 10.1073/pnas.95.19.11235
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of cloned plasma membrane proteins by freeze-fracture electron microscopy

Abstract: We have used freeze-fracture electron microscopy to examine the oligomeric structure and molecular asymmetry of integral plasma membrane proteins. Recombinant plasma membrane proteins were functionally expressed in Xenopus laevis oocytes, and the dimensions of their freezefracture particles were analyzed. To characterize the freezefracture particles, we compared the particle cross-sectional area of proteins with ␣-helical transmembrane domains (opsin, aquaporin 1, and a connexin) with their area obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
182
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 43 publications
14
182
0
Order By: Relevance
“…It has been shown that large proteins appear in freeze fractures as particles having crosssectional areas that vary linearly with the number of membrane-spanning helices, by a factor of 1.4 nm 2 per helix (Eskandari et al, 1998). In the same study, connexin hemichannels, ion channels, a water channel, and a co-transporter were all visible by freeze fracture.…”
Section: Discussionmentioning
confidence: 61%
“…It has been shown that large proteins appear in freeze fractures as particles having crosssectional areas that vary linearly with the number of membrane-spanning helices, by a factor of 1.4 nm 2 per helix (Eskandari et al, 1998). In the same study, connexin hemichannels, ion channels, a water channel, and a co-transporter were all visible by freeze fracture.…”
Section: Discussionmentioning
confidence: 61%
“…This was explained by a dominant negative effect of the missense mutation on the GLUT2 hexamer. Such an effect might not play a role in sodium-dependent transporters because freeze-fracture electron microscopic studies have suggested that they function as monomers (29).…”
Section: Discussionmentioning
confidence: 99%
“…SDS) or that the CFTR dimers only represent a small percentage of the total CFTR proteins that could not be detected by the co-immunoprecipitation procedure. A recent study by Eskandari et al (22) established structural evidence for a dimeric complex with the CFTR proteins. These investigators used freeze fracture electron microscopy to investigate the oligomeric assembly of membrane proteins expressed in Xenopus oocytes, and they concluded that the intramembrane structure of CFTR was consistent with a dimeric assembly of 12-transmembrane helix of the CFTR monomers.…”
Section: A-s-l-v-p-r-g-s-g-g-g-g) As Shown Inmentioning
confidence: 99%